Exploring the Impact of Strut Geometry on Strut-Braced Wing Configurations - Mihai-Vlăduț Hothazie; Daniel-Eugeniu Crunțeanu; Mihai-Victor Pricop; Ionuț Bunescu (Aerospace, 2025)
The anticipated growth of the aviation industry has driven regulators to establish stringent targets for achieving net-zero greenhouse gas emissions, which are challenging to meet with conventional aircraft configurations. The strut-braced wing configuration has emerged as a promising alternative for improving aerodynamic efficiency. This study investigates the aerodynamic performance of such a configuration using a high-fidelity computational fluid dynamics analysis, conducted in two phases. The first phase involves a parametric study examining the effects of two key parameters: the length and the tilt angle of the strut’s elbow. The reference configuration is based on the strut braced wing configuration from the Platform for Aircraft Drag Reduction Innovation workshop. Building on the insights from the parametric study, the second phase involves an optimization of the strut’s geometry, focusing on minimizing aerodynamic drag. The results demonstrate an 11.5% reduction in the drag coefficient while maintaining the same lift coefficient, primarily attributed to a decrease in shockwave interactions within the strut–wing gap. These findings, combined with the parametric study, provide valuable insights into the influence of strut geometric parameters on drag minimization, highlighting their potential role in advancing sustainable aircraft design.